An Identification key to the species of Auchenorrhyncha of Iranian fauna recorded as pests in orchards and a review on the pest status of the species - Mozaffarian, Fariba (Zootaxa, 2018)
An illustrated dichotomous identification key for a total of 54 Auchenorrhyncha species of Iran is presented. The studied species have been recorded as pests and vectors of diseases to fruit trees. Twenty nine records were contributed to Iranian orchards and 25 of which were from other parts of the world. Hence, the latter group can be considered as potential pests and vectors in Iran. Reviewing the published information on the former group suggests 12 species as pests (4, 2 and 6 species with significant, minor, and unknown recorded economic damage levels, respectively). The pest status of 14 recorded pest species were quite doubtful and 3 of them could not be present in Iran due to the lack of evidence or their limited distribution in other parts of the world. The 4 species which were recognized as well known and significantly important pests belonged to the families: Tropiduchidae (Ommatissus lybicus Bergevin, 1930), Cicadidae (Cicadatra alhageos (Kolenati, 1857)), and Cicadellidae (Hishimonus phycitis (Distant, 1908) and Neoaliturus haematoceps (Mulstant et Rey, 1855)). One species Orosanga japonicus is recording for the first time from Iran and added to the key.